Likwidacja wojewódzkich funduszy ochrony środowiska i gospodarki wodnej a funkcjonowanie systemu udzielania pomocy publicznej na ochronę środowiska - Bartczak, Bartosz (Liquidation of regional funds for environmental protection and water management versus the system of granting state aid to environment protection, 2008)
Regional Funds for Environmental Protection and Water Management are the second most important subject which gives state aid for environment protection in Poland. Recently attempts to liquidate this ford have been made. The aim of this article is to show the role of regional funds in the area of granting state aid for environment in Poland. This article also shows what consequences for Polish system of granting state aid of environment protection their liquidation could have.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 22, s. 13-22